Mortality, Morbidity, and Prognostic Factors in the Surgical Resection of Brain Metastases: A Contemporary Cohort Study - Picarelli, Helder; Oliveira, Marcelo de Lima; Marta, Gustavo Nader; Solla, Davi J. Fontoura; Teixeira, Manoel Jacobsen; Figueiredo, Eberval Gadelha (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Objective Despite advances in systemic therapy and radiotherapy (RT), neurosurgical resection (NSR) remains a mainstay of the treatment of brain metastases (BMs). Although it is unequivocal in instances of diagnostic doubt, radioresistance, and risk of death due to neurologic causes, NSR may be controversial in other situations. Many aspects related to NSR have not yet been well established, and the primary prognostic indices were proposed only in the last decade. This study evaluates the survival and the morbidity, causes of death, prognostic factors, and the impact of RT in patients with BMs treated by NSR in the current era.Methods A total of 200 patients with BMs who were treated by NSR were evaluated sequentially and followed prospectively. We used logistic regression and Cox regression models to identify independent factors associated with mortality at 4 weeks and at 1 year, respectively. Clinical features, morbidity, recurrence, and causes of death were also studied.Results Lung cancer was the most prevalent cancer (36.5%); the median Karnofsky Performance Status (KPS) score was 60. Total resection was achieved in 89%, and adjuvant RT was applied in 63% of the cases. The rates of surgical mortality, morbidity, and mortality at 4 weeks were 1.5%, 17%, and 7.5%, respectively. Systemic infections were the leading cause of death in 62.5% of the cases. The median survival was 5 months, and 34.5% of patients lived > 1 year. The postoperative KPS (KPSpo) score remained unchanged or improved in 94.5% of the cases. In the multivariate analysis, a KPSpo score ≥ 80 and the application of adjuvant RT were associated with a lower risk of death at 12 weeks and at 1 year. Interestingly, the variables of primary tumor site, number of BMs, and presence of carcinomatous meningitis were not significant.Conclusion Morbidity and mortality were high, a third of the patients lived > 1 year, and the KPS score improved or remained unchanged in most cases. Prognostic indices and health conditions were important predictive factors, but the KPSpo score and adjuvant RT were independent variables for survival at 12 weeks and at 1 year. Therefore, new studies are needed to assess the influence of new therapies and specific molecular profiles.
Keywords: surgery resection of brain metastases; prognostic factors; mortality; survival; morbidity